Operation last chance : one man's quest to bring Nazi criminals to justice - Zuroff, Efraim, 1948- 1948- (Palgrave Macmillan, 2009)
The gripping personal journey of the world's last Nazi hunter as he scours the globe looking for the men and women responsible for the atrocities of the Holocaust.